Temporality of Movements of Northern Baikal Reindeer Herders, Hunters and Fishermen - Vladimir Davydov (Journal of Ethnology and Folkloristics)
This article addresses the topic of temporality of movement among northern Baikal reindeer herders, hunters, and fishermen. It proposes the distinction between short-term and long-term movements based on the return to places of intensive use. Short-term movements usually do not cover large distances and imply a return to the same place within a relatively short period of time. This type of movement implies the use of one main point where a movement starts and finishes. In contrast to short-term movements, long-term movements require intensive preparation, imply the use of several bases and cover larger distances. They are built upon a set of short-term movements which involve return to certain points of a route from which people operate. Hunting and reindeer herding are not connected only to movement in the taiga; these activities imply the use of stationary and mobile structures and hunting bases. In this context, the village also functions as a kind of base and serves as a point of constant return.